Bookkeeping to Professional Accounting: A University Power in Indonesia - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2000)
The paper is historical. lt explores the development of accounting from the mode of ‘bookkeeping’ knowledge to a ‘new’ disciplinary power of accounting in lndonesia. lt argues that after the independence of the Republic of Indonesia, 17 August 1945, a radical change of an accounting education discipline from the Dutch political administration to the indigenous Indonesian management was the main issue to a ‘new’ university system. The university became a ‘powerful’ system to transform bookkeeping tradition to accounting profession.